Age Related Histo-morphological changes of Splenic connective Tissue in Goat (Capra Hircus) - Waghaye, JY; Banubakode, SB; Charjan, Rupali; Rana, Jigyasa; Nadeshwar, NC; Mainde, UP (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted on 40 spleen samples of goat from prenatal to four months and above age. The small pieces from spleen were processed for histo-morphological study. The general histo-architecture of spleen showed capsule, trabeculae, red pulp and white pulp in all age groups. The splenic capsule was found to be composed of outer fibrous layer and inner muscular layer. The thickness of capsule was gradually increasing due to increase in thickness of muscular layer with the advancement of age. The components of outer fibrous layer were wavy and intermingled with collagen, reticular and elastic fibres. The elastic fibres however, became short and fragmented with advancement of age. Variation in the concentration of these fibres in capsule with advancement of age was necessary to provide firmness to the organs from outside during postnatal period and to provide elasticity of organ during prenatal and early postnatal stage. The connective tissue trabeculae radiated from capsule in to splenic pulp and supported the blood vessels. The components of trabeculae were similar to that of capsule.
Keywords: Histo-morphological Changes; Spleen; Goat